Etnografando a Paisagem Sertão - SILVA, Margarida do Amaral (2011)
This research presents an approach to the fact that the hinterland is a cultural phenomenon that promotes the landscape, giving the Brazil-interior settings. With a view to assessing content endlessly reissued, the handling of stories about the backcountry led an exercise in theoretical and conceptual experimentation. Taking as study material from cuttings of literary exponents as Hugo de Carvalho Ramos, Bernardo Elis, João Acciole, Léo Godoy Otero, Eli Brasiliense, Mário Rizério Leite, Affonso Arinos and Carmo Bernardes, as well as the pictorial work of Issac Alarcão, the travelogue of Augusta de Faro Fleury Curado, and iconographic, cartographic and/or historiographical material about markers on the backwoods as the troops, the car steers, the cattle, the ranch and their own swing, what happened was an opportunity for review of the place and time temporalized spatialized in discursive productions. To expose the composition of the place were covered projections of a fluctuating space and unfinished. To be noticed and be a prospective way, the hinterland is assessed in this study provide the thematic nature (and often dramatic) the achievements of the discursive landscape hinterland. It was necessary to exercise a juxtaposition of content that mediate permeate the place, which unfolds according to the descriptive labels that strengthen the region invented by very different perspectives narratives. More narrowly, it longed to be interpreted as a manifestation of the interior landscape imagined place, multi-experiencied, interactive and pregnant women, which is always becoming.